ANALYSIS OF THE INFLUENCE OF ROLL SURFACE PROFILE ON THE NATURE OF SELF-OSCILLATIONS OF THE WHEELSET - Verbytskyi, V. H.; Demchenko, V. O. (Science and Transport Progress, 2004)
The conditions of dangerous-safe loss of stability defined only by geometry of wheel profile. At certain geometry of wheel self-oscillations exist at supercritical speeds more; the stable limit cycle in this case limits growth of perturbations that corresponds to safe loss of stability. At infringement of some relationship of parameters of the wheel profile the unstable limiting cycle limits area of stability of rectilinear motion already at speeds less critical, narrowing an interval of operational speed; at speeds more critical growth of perturbations will be unlimited - a case of dangerous loss of stability.